2008
DOI: 10.1111/j.1365-3040.2008.01866.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechano‐perception in Chara cells: the influence of salinity and calcium on touch‐activated receptor potentials, action potentials and ion transport

Abstract: This paper investigates the impact of increased salinity on touch-induced receptor and action potentials of]ext was high, the background conductance increased to a lesser extent and proton pump currents were stimulated, establishing a PD narrowly negative to APthreshold. Cells did not spontaneously fire, but became hypersensitive to touch. Even slight touch stimulus induced an action potential and further repetitive firing. The duration of each excitation was extended when [Ca 2+ ]ext was low. Cell viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 77 publications
1
46
0
Order By: Relevance
“…reached certain level of depolarization after application of those compounds. As proposed by V. Sheperd and colleagues [18], this repetitive firing resembles the onset of a critical instability where a time-ordered structure (repetitive firing) emerged after ramping currents to the excitation threshold. Namely, increased background conductance combined with loss of proton pump activity caused gradual depolarization of cell membrane potential to AP threshold.…”
Section: The Effect Of Acetylcholine On Single Action Potentialmentioning
confidence: 90%
“…reached certain level of depolarization after application of those compounds. As proposed by V. Sheperd and colleagues [18], this repetitive firing resembles the onset of a critical instability where a time-ordered structure (repetitive firing) emerged after ramping currents to the excitation threshold. Namely, increased background conductance combined with loss of proton pump activity caused gradual depolarization of cell membrane potential to AP threshold.…”
Section: The Effect Of Acetylcholine On Single Action Potentialmentioning
confidence: 90%
“…In plasmolysed cells, the membrane loses connection with the cell wall and this might explain the lack of sensitivity. Shepherd et al (2002Shepherd et al ( , 2008 speculated that reduced turgor (before plasmolysis) and greater sensitivity to stimulation is part of a defensive mechanism that isolates injured cells from the rest of the plant. This is discussed in greater detail in Sect.…”
Section: Ea Eb Ec a B Cmentioning
confidence: 99%
“…The authors also tracked the movement of the stimulator and found "surface relaxation" following the strike or its withdrawal. (Shimmen 1997b Shepherd et al (2001) investigated the effect of decreased turgor on both RPDs and mechanically induced APs. The turgor covered the range from 0.6 MPa to 0.24 MPa.…”
Section: Ea Eb Ec a B Cmentioning
confidence: 99%
See 2 more Smart Citations